(untitled) (Praxis Educativa, 2015)
Masters in Education have become a teaching training option for Upper Secondary and Higher Education in Mexico. The professional guidelines in postgraduate studies are one of the options recognized by the National Council for Science and Technology in Mexico (conacyt) for quality postgraduate studies, along with those aimed at research. The study presented here provides elements to clarify the meaning of professionalizing guidelines in postgraduate educational studies, from a qualitative approach that describes training practices and meanings that the protagonists give to the teaching professionalization. We analyze practices observed in nine class sessions -in a Master of Education focused on innovation and the use of Information and Communications Technology- together with the sense of gradualness on the way to teachers´ autonomy.